HUBUNGAN KEBIASAAN BELAJAR DENGAN PRESTASI BELAJAR SISWA MATA PELAJARAN MATEMATIKA KELAS V SDN 6 CENDONO - Norma Dini Filsafati; Siti Lutfiyah; Ary Delia Maqfiroh; Axl Yudhistira; Fitriyah Amaliyah (Jurnal PGSD Musi, 2023)
Study habits are techniques or ways that exist in students in receiving learning, doing assignments and managing time in completing an activity. This study aims to determine whether or not there is a relationship between study habits and student achievement in mathematics class V SDN 6 Cendono. This type of research is quantitative research using correlational analysis techniques. The data analysis technique in this study uses product moment correlation. Data collection techniques used in this study were questionnaires and documentation. Study habits data were obtained from the angle while learning achievement data was obtained through documentation. Data processing is carried out after the prerequisite test is carried out in the form of a data normality test. The results of this study showed that the correlation coefficient r calculated was -0.140 and the sig.(2-tailed) value was 0.429 > 0.05, so ????????was accepted. Thus it can be concluded that there is no significant relationship between study habits and student achievement in mathematics class V SDN 6 Cendono. In this study the relationship between the two variables is very weak and negative, which means they have a relationship that is not opposite or opposite.